2021
DOI: 10.3390/cancers13184574
|View full text |Cite
|
Sign up to set email alerts
|

The Reality of Lung Cancer Paradox: The Impact of Body Mass Index on Long-Term Survival of Resected Lung Cancer. A French Nationwide Analysis from the Epithor Database

Abstract: Obesity could have a protective effect in patients with lung cancer. We assessed the prognostic role of preoperative BMI on survival in patients who underwent lung resection for NSCLC. A total of 54,631 consecutive patients with resectable lung cancer within a 15-year period were extracted from Epithor (the French Society of Thoracic and Cardiovascular Surgery database). Patient subgroups were defined according to body mass index (BMI): underweight (BMI < 18.5 kg/m2), normal weight (18.5 ≤ BMI < 25 kg/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Like our findings for the stage of disease, most risk factors identified in our study as predictors of late survival have also been identified as affecting shorter term (5 or 10-year) survival rates, in particular: age [ 22 , 31 ], chronic bronchitis [ 35 ], COPD [ 6 , 17 ] FEV1% [ 10 , 17 , 22 ], smoking history [ 22 ] or cumulative smoking [ 9 , 10 , 17 , 22 , 31 ], nutritional status [ 22 ], BMI [ 12 ], weight loss [ 14 ], and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Like our findings for the stage of disease, most risk factors identified in our study as predictors of late survival have also been identified as affecting shorter term (5 or 10-year) survival rates, in particular: age [ 22 , 31 ], chronic bronchitis [ 35 ], COPD [ 6 , 17 ] FEV1% [ 10 , 17 , 22 ], smoking history [ 22 ] or cumulative smoking [ 9 , 10 , 17 , 22 , 31 ], nutritional status [ 22 ], BMI [ 12 ], weight loss [ 14 ], and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to very long-term survival, the same cohort was used as in previous studies with a 5- to 7-year follow-up assessment [ 14 , 32 , 35 ]. We updated data on later vital status by direct interrogation (in April 2021) of the French INSEE (Institut National de la Statistique et des Etudes Economiques) open-source national database (i.e., open-link Internet), which is already used for the assessment of lung cancer survival after surgical treatment by the French Epithor team [ 12 ]. The INSEE database is not exhaustive for foreign patients (even those having spent a long period in France), so among those patients born outside France, we considered as dead those stated as dead in the INSEE database, but we excluded the remaining cases from the study ( n = 25).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations